Evaluation of the Relationship Between Hashimoto's Thyroiditis and the Course of COVID-19 Infection - Hasret Cengiz; Taner Demirci; Ceyhun Varım (Sakarya Tıp Dergisi, 2021)
Objectives: Coronavirus infection (COVID-19) has caused a worldwide pandemic and affected many systems. Hashimoto's Thyroiditis is one of the most common diseases in the community and is the prototype of autoimmune thyroid diseases. It is unknown how thyroid autoimmunity and thyroid dysfunction will affect the course of COVID-19. The aim of this study is to show the course of this infection in patients with Hashimoto's Thyroiditis. Materials and Methods: A descriptive study was conducted in which adult patients with Hashimoto's Thyroiditis who received COVID-19 infection from April to October 2020 in our center were recruited retrospectivelly. Those with severe comorbid conditions that may affect the course of the disease,and using immunomodulatory and immunosuppressive drugs, and pregnant women were not included in the study. Results: A total of 232 patients included. Median (IQR=interquartile) age value was 43 (34-54), and the male/female ratio was 21/211 (9.1%/90.9%). In our study, mortality due to COVID-19 in our patients was found to be consistent with the normal population in their age group (1,7%, n:4), and 7 patients were treated in the intensive care unit. A significant negative correlation was found between Anti-Tyroglobuline Antibody (Anti-Tg) and White Blood Cell (WBC) (r=-0.189, p=0.041), Neutrophil (r=-0.191, p=0.040), Neutrophil to Lymphocyte Ratio (NLR) (r=-0.244, p=0.008), Ferritin (r=-0.259, p=0.042). Conclusion: The rate of patients with supressed Thyroid Stimulating Hormone (TSH) in intensive care unit was slightly higher, but since the number of events was low, this finding could not gain significance. Most patients with Hashimoto's Thyroiditis have had a mild infection. Thyroid autoimmunity does not appear to affect the COVID-19 infection’s course.